Green School Model: Best Practices from the Field on Education for Sustainability in India - Ahmad, Prof. Jasim; Arora, Meenal (Voices of Teachers and Teacher Educators, 2021)
Today’s education must respond to the new 2030 Agenda for Sustainable Development by preparing young generations to deal with challenges such as poverty, hunger, inequality, climate change, loss of biodiversity, and natural resource depletion, resulting in negative consequences on human health and livelihood. To achieve this, UNESCO has been promoting Education for Sustainable Development (ESD) since 1992. It led to the UN Decade for ESD from 2005 to 2014 and is now directing its efforts towards the Global Action Programme (GAP) on ESD. A Green School is a school that prioritizes energy, waste, water, food, and biodiversity management in its governance, teaching and learning practices, community partnerships and facilities and operations of the school. The purpose of a Green School is to help students understand our impact on the planet and how to address the colossal social, economic, and environmental problems that we face today. A Green School provides a dynamic and vibrant learning environment as it addresses real-life challenges by practising and modelling sustainability in all aspects. To achieve this, more and more schools are adopting initiatives on five major themes: energy, water, waste, food, and biodiversity, thus empowering various stakeholders to embark on the journey towards sustainable development. The study draws its result using both secondary as well as primary data collected through the tools developed by the researcher. The study is exploratory in nature and presents the analysis on a thematic framework highlighting the strategies that schools can easily adopt to become Green Schools.